A multimodality imaging approach for guiding a modified endovascular coil embolization of a single intrahepatic portosystemic shunt in dogs. (December 2015) - Knapp, Teja; Navalòn, Iolanda; Medda, Massimo; Pradelli, Danitza; Borgonovo, Simone; Crosta, Cristina; Bussadori, Claudio Maria
Abstract: Intrahepatic portosystemic shunts (IHPSS) in dogs are aberrant vascular anomalies that connect the portal and the systemic venous vessels. In most of the patients, the surgical approach is unfavourable due to the difficulties in isolating the IHPSS, making the option of a percutaneous transvenous coil embolization (PTCE) one of the safer occlusive procedures. This study describes the treatment of eight dogs with a single IHPSS using a multimodality imaging approach to guide the modified PTCE procedure. This new technique results in a decrease of 71% of the time of the entire procedure with the reduction of 91% in the time required involved the IHPSS identification and in the fluoroscopy exposure time avoiding the need for iodinated contrast agents during the procedure. Moreover, the placement of the catheter before the caval stent ensures its greater stability, enhancing the procedural safety in the phase when the coils are released and avoiding the risk of their dislocation. Highlights: MIA guides the modified PTCE of single intrahepatic portosystemic shunt in dogs. Procedure was monitored by TEU and the spot use of the fluoroscopy. TEU gave the qualitative blood flow analysis pre- and post-PTCE attenuation. Modified PTCE reduced the fluoroscopy exposure time avoiding the contrast agent's use. MIA enhanced the procedural safety in the coils release phase.